A comparative study on the prevalence and bone characteristics of tibial dyschondroplasia between Cobb 500 and Ross 308 breeds of broiler chickens from four selected broiler farms in Terengganu - Mohd Farhanuddin Kadir@Salleh
Tibial dyschondroplasia (TD) is one of the major causes of lameness in broiler chicken. It is characterized by the presence of a non-vascularized, non-mineralized lesion that extend from the epiphyseal growth plate into the metaphysis of the proximal region of tibiotarsus and femur bones. A study was conducted to compare the prevalence and bone characteristics of TD between Cobb 500 and Ross 308 breeds of broiler chicken from four selected broiler farms in Terengganu (two closed and two open-sided houses). Twenty eight Cobb 500 and twenty eight Ross 308 broiler chicken were randomly selected from each of the houses. All broiler chicken were reared under the same management system commonly applied in commercial broiler farms, with provision of feed and water ad libitum and light for 23h a day during the entire rearing period. Broiler chicken were distributed in a completely randomized experimental design with factorial arrangement of 2 breeds, and housing systems. At 35 days, all broiler chickens were sacrificed by cervical dislocation. Immediately, the right tibiotarsus of all broilers was removed to determine the severity of TD by gross scoring and histopathology. Ten birds from each sample within each gross score were selected for tibiotarsus characteristic and determination of bone calcium and phosphorus levels. Broiler chickens reared in closed house showed significantly higher prevalance of TD compared to those in the open-sided house. In the closed house, the prevalence of TD for Cobb 500 and Ross 308 was 50% and 35.7% respectively whereas in the open-sided house the prevelence was 7.1% for both breeds. In contrary, there was no significant interaction observed between TD and breed of broilers. Tibial dyschondroplasia had no effect on the length, weight, robusticity index and strength of the tibiotarsus. However, broiler chickens affected with TD had significantly lower calcium and significantly higher phosphorus tibiotarsus bone levels than those unaffected.